2007
DOI: 10.1080/10256010701562794
|View full text |Cite
|
Sign up to set email alerts
|

Radioactivity levels in some wild edible mushroom species in Turkey

Abstract: Eleven different wild-growing edible mushroom species collected from various regions of Turkey were analysed for their content of 137Cs, 40K, 226Ra and 232Th using a high-resolution gamma-ray spectrometry. Specific activities of 226Ra and 232Th were generally below detection limits. The specific activities of 137Cs and 40K ranged from 2.4+/-0.3 to 109.0+/-7.3 Bq kg-1 with a mean of 28.4+/-27.2 Bq kg-1 (dry matter) and 715.5+/-50.1 to 1779.0+/-163.7 Bq kg-1 with a mean of 1150.8+/-315.2 Bq kg-1 (dry matter), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
0
15
4
Order By: Relevance
“…Several authors have reported activities of U and Th isotopes in macrofungi (Mietelski et al 2002;Wichterey and Sawallisch 2002;Baeza and Guillén 2006;Turhan et al 2007). In general, activities of 234 U, 238 U, 228 Th, 230 Th and 232 Th in macrofungi from background areas were below 10 Bq kg -1 (dry weight).…”
Section: Uranium and Thoriummentioning
confidence: 96%
“…Several authors have reported activities of U and Th isotopes in macrofungi (Mietelski et al 2002;Wichterey and Sawallisch 2002;Baeza and Guillén 2006;Turhan et al 2007). In general, activities of 234 U, 238 U, 228 Th, 230 Th and 232 Th in macrofungi from background areas were below 10 Bq kg -1 (dry weight).…”
Section: Uranium and Thoriummentioning
confidence: 96%
“…We believe it is important to underline that information relating thorium with mushrooms is scarce (Baeza and Guillén 2006;Turhan et al 2007) and there are no conclusive data on Th concentration in fungal carpophores. It was quite interesting to observe that the highest values were detected in two species (H. fasciculare and G. spectabilis) that live on wood.…”
Section: Found Lowmentioning
confidence: 97%
“…Despite the fact that some authors have previously reported the presence of radionuclides in mushrooms (Kalac 2001;Turhan et al 2007), they have generally investigated isotopes of cesium, lead, radium, thorium and others, but not uranium. Only the papers of Baeza and Guillén (2006) relate the content of U to mushrooms with the bioavailability of the soil mineral substrate or with the degree of maturity of mushrooms.…”
Section: Found Lowmentioning
confidence: 97%
“…Mushroom and soil samples were crushed for passing a 40 mm mesh sieve. They were then transferred to an uncontaminated empty plastic cylindrical container of uniform size (50 mm in height, 60 mm in diameter) and sealed for a period of 4 weeks in order to allow for radon and its short-lived progenies to reach secular radioactive equilibrium prior to gamma spectroscopy (Turhan et al, 2007).…”
Section: Samples Preparationmentioning
confidence: 99%